Values Based Superior Students’ Learning Behaviour - Nadhirin, N (ADDIN, 2018)
The purpose of this research is to find (1) organizational behavior in superior school students learn (2) the source of values that underlies the attitude and behavior of superior student learning (3) superior student learning behavior in school and (4) learning interaction between teacher and student excel at school. This research uses qualitative approach and pospositivistic paradigm. The research data was collected by interview, observation and documentation. Technique of validity test data use triangulation, cover angulasi technique, source and time. Data were analyzed by Miles Hubermans interactive cycling technique, with cycle collecting, reducting, displaying and verifying. The subjects of this research are the leaders of madrasah, faculty, students and stakelholders of madrasah. Research location at MA. NU Banat, Kudus, Central Java, Indonesia. The results of this study are (1) Students who have good pretation in the field of academic and non academic are students who study in school organization unit that has commitment and spirit to go forward. A good and conducive organizational culture that is maintained by all members of the organization is very supportive to the achievement of superior and competitive student achievement (2) The source of values or outlooks that make the students become outstanding achievers is the accumulation of values formed from the religious family environment and dicipline, school environment consistent with the practice of religion in the school environment that inculcates values of virtue, dicipline in learning, honest, competitive and heed the norms prevailing in society. (3) behavioral typology and high school student learning attitudes are responsive stimuli. The more rules and structured tasks created by the school and the subject teachers, the students' attitudes and motivation will be more intense and vice versa (4) outstanding achievement students have a close relationship with the teacher. Teachers for students who excel are teachers who are not only as parents, as mentors, as well as teachers who can put themselves as friends of students, who can be invited to communicate closely and there is openness in various problems and teachers help students to solve problems encountered so that good achievement is greatly assisted by his teachers who are concerned primarily on non-academic issues.